Ergonomists' experiences of executing occupational health surveillance for workers exposed to hand-intensive work: a qualitative exploration - Kristina Eliasson; Anncristine Fjellman-Wiklund; Gunilla Dahlgren; Therese Hellman; Magnus Svartengren; Teresia Nyman; Charlotte Lewis (BMC, 2022)
Abstract Background In order to reduce work-related upper limb disorders, the Swedish Work Environment Authority introduced an occupational health surveillance targeting hand-intensive work. A process model, aimed at supporting the employers as well as the occupational health service provider (i.e., ergonomist) in the work process with the occupational health surveillance, was developed. The objective of this qualitative study was to explore ergonomists' experiences of the execution of occupational health surveillance for hand-intensive work when following the novel process model as well as factors influencing the execution. Methods Semi-structured individual interviews were conducted with ten ergonomists on one occasion regarding their experience of following the work process. Qualitative content analysis with an inductive approach was used for analyzing the data. Results The ergonomists' experiences were summarized in one theme "A joint roadmap supporting a participatory process" and two categories "Clear structure provided by the components" and "The process influenced by collaboration and context". The ergonomists valued being guided by the systematics of the model, which provided structure and clarity in their work. Factors affecting the execution were related to communication deficiencies and uncertainties regarding expectations between different roles and functions (e.g., ergonomists and contact person, lack of information to workers). Additional factors, for instance, companies' routines and the ergonomist's intra-organizational support, such as access to IT-resources, could also affect the process. Conclusions The findings reveal that this process model facilitates the ergonomists' work and cooperation with a client company. However, the process model needs to be developed and accompanied by a guideline with information related to the process, including e.g., description of a start-up meeting and of the roles/functions of the involved parties.